2006
DOI: 10.1097/01.wnr.0000227993.07799.a2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic targeting of bone marrow stromal cells into spinal cord: through cerebrospinal fluid

Abstract: We established a new magnetic targeting system in which bone marrow stromal cells migrate through the cerebrospinal fluid to the desired site in the spinal cord in rats. Subarachnoid injection has been reported as a minimally invasive method of transplantation of bone marrow stromal cells for spinal cord injury. It may be, however, less effective than direct injection into the spinal cord in terms of cell delivery. After implantation of a magnet, subarachnoid injection of bone marrow stromal cells labeled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 16 publications
1
44
0
4
Order By: Relevance
“…The cells circulating in the subarachnoid space were gathered under the magnetic implant. This correlates well with the study of Nishida et al 26 These authors measured the area of GFPpositive cells in the healthy spinal cord under a magnetic implant (5 mm in diameter, 3 mm in height, 350 mT) after the administration of SPION-labeled cells via lumbar puncture and reported a higher concentration of cells in the subarachnoid space below the magnetic implant one day after intrathecal transplantation. In contrast to Nishida et al, we directly counted the number of implanted cells instead of measuring the GFP-positive area, a more accurate approach to determining the number of cells and the cell distribution in the lesion site.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The cells circulating in the subarachnoid space were gathered under the magnetic implant. This correlates well with the study of Nishida et al 26 These authors measured the area of GFPpositive cells in the healthy spinal cord under a magnetic implant (5 mm in diameter, 3 mm in height, 350 mT) after the administration of SPION-labeled cells via lumbar puncture and reported a higher concentration of cells in the subarachnoid space below the magnetic implant one day after intrathecal transplantation. In contrast to Nishida et al, we directly counted the number of implanted cells instead of measuring the GFP-positive area, a more accurate approach to determining the number of cells and the cell distribution in the lesion site.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in this area have focused on targeting cells into the liver 24 or injured brain 25 or have evaluated the homing of cells into the healthy spinal cord with the use of a magnetic system based on a permanent magnet. 26 However, a more detailed evaluation of such magnetic systems is often missing in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…15,[71][72][73] The data and images shown in Figure 1 illustrate the high proportion of bone marrowderived mesenchymal stem cells labeled with SPIONs. In addition to the stem cell tracking, SPIONs have also been used to magnetically target stem cells to lesion sites, as described by Nishida et al 77 Hamasaki et al, 78 successfully showed, in organotypic cultures, the possibility of enhancing axon formation by magnetically localizing SPION-labeled cells. Studies on the use of SPIONs to focus the delivery of stem cells to specific areas are still being conducted, and have been published by Cheng et al 79 …”
Section: Tracking Stem Cells With Superparamagnetic Iron Oxide Nanopamentioning
confidence: 99%
“…In the NP and NP + MF groups, a 2 mm sample of 25 µg/mL IONPs embedded in 3% agarose hydrogel was implanted at the site of injury during surgery, whereas only gel was implanted in the SCI and MF groups. 37,38 The rats were injected subcutaneously with 5 mL of saline to prevent dehydration and injected intramuscularly with gentamicin-cefazolin 20 mg/kg for five days following surgery. 39 The urinary bladder was manually evacuated thrice daily until spontaneous voiding was achieved.…”
Section: Surgerymentioning
confidence: 99%